2013
DOI: 10.1136/bmjopen-2013-002937
|View full text |Cite
|
Sign up to set email alerts
|

Can nutrition be promoted through agriculture-led food price policies? A systematic review

Abstract: ObjectiveTo systematically review the available evidence on whether national or international agricultural policies that directly affect the price of food influence the prevalence rates of undernutrition or nutrition-related chronic disease in children and adults.DesignSystematic review.SettingGlobal.Search strategyWe systematically searched five databases for published literature (MEDLINE, EconLit, Agricola, AgEcon Search, Scopus) and systematically browsed other databases and relevant organisational websites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The main arguments against farm policies playing a role are: (i) subsidies have a mixed effect on the prices and production outputs of various food items (33,34,36) ; (ii) the impacts on commodity prices offer savings to the food industry, but have little effect on food costs at retail and even less on those prices passed on to consumers (35) ; (iii) food consumption is relatively unresponsive to changes in market prices and so the very small food price changes induced by farm subsidies could not have had large effects on food consumption patterns (34) ; and (iv) food consumption has not previously changed markedly in response to policy-induced adjustments in relative prices (32) . However, ecological studies and public health commentaries suggest that farm policies do matter for health (12,13,(37)(38)(39) . Since agricultural policy changes in the 1970s (the origin for today's policies), food supplythe amount of energy available to the population -has increased from 9075 kJ (2169 kcal)/person per d in 1970 to 10 853 kJ (2594 kcal)/person per d in 2009 (40) , with the largest increase seen in refined grains (782 kJ (187 kcal)) and added fats and oils (703 kJ (168 kcal)).…”
Section: Discussionmentioning
confidence: 99%
“…The main arguments against farm policies playing a role are: (i) subsidies have a mixed effect on the prices and production outputs of various food items (33,34,36) ; (ii) the impacts on commodity prices offer savings to the food industry, but have little effect on food costs at retail and even less on those prices passed on to consumers (35) ; (iii) food consumption is relatively unresponsive to changes in market prices and so the very small food price changes induced by farm subsidies could not have had large effects on food consumption patterns (34) ; and (iv) food consumption has not previously changed markedly in response to policy-induced adjustments in relative prices (32) . However, ecological studies and public health commentaries suggest that farm policies do matter for health (12,13,(37)(38)(39) . Since agricultural policy changes in the 1970s (the origin for today's policies), food supplythe amount of energy available to the population -has increased from 9075 kJ (2169 kcal)/person per d in 1970 to 10 853 kJ (2594 kcal)/person per d in 2009 (40) , with the largest increase seen in refined grains (782 kJ (187 kcal)) and added fats and oils (703 kJ (168 kcal)).…”
Section: Discussionmentioning
confidence: 99%
“…This was in an environment of increasing housing and fuel costs as well. Take in Tables 2 and 3 Dangour et al (2013) assert that despite changes in food prices having an impact on the quantity and quality of food consumed, food price policies and the nutritional status of a given population are separated by many lengthy pathways of influence. They propose that a range of factors such as genetic predisposition, income level, urban or rural residence, education of household head and women's control of income also mediate the process.…”
mentioning
confidence: 99%
“…An attempt to synthesize 'current evidence of agriculture-to-nutrition linkages' through a study of ten reviews published since 2000 including [8] and [9] concluded that expectations on the potential for nutrition impact have to be set rationally and such initiatives should have high standards of research and communication, which currently seemed to be lacking [10]. A separate systematic review of the evidence of the agriculture food price pathway on nutrition outcomes surmised that 'developing credible impact evaluations for the effect of a food and agricultural policy on the nutrition status of individuals and populations is extremely challenging', and called for focus on 'cross-sectoral evidence generation' (p. 7) [11]. A review of nutritional effects of programmes in four different sectors including agriculture flagged poor quality evaluations and the need for rigorous effectiveness assessments [6].…”
Section: Introductionmentioning
confidence: 99%